Care pattern and behavioural status of preschool children of employed mothers in MOH area Kaduwela - D. C. Samarakkody; M. W. Gunathunga (College of Community Physicians of Sri Lanka, 2005)
Introduction The objective of this study was to assess the in fluence of care patterns on behavioural status of pre school children of employed mothers.   Methodology A descriptive cross sectional study was con ducted to assess the influence of care patterns, on behaviour of pre school children of employed mothers in the MOH area, Kaduwela. Parents or principal care givers of pre-school children getting two types of care (home care and in day care centers) were interviewed using a pre-tested, interviewer administered questionnaire.   Results The educational level of the caregivers of the day care group was significantly higher than the home care group. The prevalence of behaviour abnormalities of the study group was 10.75%. The study revealed a significantly higher proportion of behavioural abnormalities among children looked after at their own home than those who were looked after in daycare centres. The children looked after in daycare centres had more advanced social interactions than the home cared group. A higher proportion of children cared at home showed abnormal behaviours related to eating, sleeping, personal interactions and communication than children looked after in day care centres. Irritability was shown by higher percent age of children looked after in day care centres.   Conclusions Pre-school children looked after in their homes showed more behavioural problems than those looked after at day care centers. The effect of care pattern on behaviour of pre-school children depends on the educational level of the substitute care giver.